The Role of Management Systems and Social Control in the Implementation Process of Performance Budgeting - Heciak , Sławomin (Studia Oeconomica Posnaniensia, 2026)
This article addresses the issues related to the need for remodelling the finance management approach, from a method where spending public funds is a goal in itself into a method of effective selection of resources (including financial ones) for the assumed targets and tasks. The article also addresses issues related to social participation in the process of state budget planning and assessment. Performance based budgeting, designed to provide higher transparency in allocating public funds, may constitute an effective instrument for the social control of government centres. The article emphasizes that performance based budgeting may contribute to higher social participation in the process of setting the priorities for spending public funds, as well as to decreasing the asymmetry of information between the centres of expenditure generation and the centres of social and institutional control. The significance of communication and monitoring has been emphasized as well as the elements of performance based budgeting that need to be reinforced in order to ensure the added value resulting from social participation.